Identificação preliminar e estado de preservação atual de bens culturais edificados da colonização holandesa em Holambra/SP - João Luiz van Ham Mello (2020)
The present work of master's thesis carries out an analysis of the built cultural heritage related to Dutch colonization, in the current municipality of Holambra, in the countryside of the state of São Paulo, Brazil. Holambra is a municipality of the Metropolitan Region of Campinas, it is known nationally by its flowers and ornamental plants production, being recognized as the “Capital of Flowers” in Brazil, also due to its largest annual event, Expoflora. The local Dutch colonization began in 1948, lasting until 1991, when it was emancipated. Tourism has been a booming activity since this period. The assumedly Dutch character of the current city environment contributes to a progressive thematization of the urban environment and thus to the forgetfulness of the original colonization landscape. In this scenario, the need to contribute to heritage studies was identified by investigating the architectural ensemble, resulting from Dutch colonization, which today is fragmented due to the lack or ineffectiveness of policies for cultural heritage at the municipal level. The study conducts an unprecedented research based on historical archives, specific bibliographies and a survey with local residents, which culminates in a defense of the built cultural heritage, identified as being in a critical state of preservation.